2023
DOI: 10.1021/acs.biomac.2c01007
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteins as a Platform for Making Proton-Conductive Free-Standing Biopolymers

Abstract: Biopolymers are an attractive environmentally friendly alternative to common synthetic polymers, whereas primarily proteins and polysaccharides are the biomacromolecules that are used for making the biopolymer. Due to the breadth of side chains of such biomacromolecules capable of participating in hydrogen bonding, proteins and polysaccharide biopolymers were also used for the making of proton-conductive biopolymers. Here, we introduce a new platform for combining the merits of both proteins and polysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
1
6
0
Order By: Relevance
“…Although the methanesulfonyl group is not an oxo-acid (in oppose to a sulfonic acid), it can still contribute to hydrogen bond formation due to the accessible lone pairs on its oxygens, hence, this is our main suggested explanation for the improved protonic conductivity following the first step of the reaction. This explanation is in line with previous studies showing that groups capable of hydrogen-bonding can support improved proton conduction across biomaterials. , Nevertheless, in our study, we cannot rule out local disruption of the collagen triple helix by adding the methanesulfonyl group to Hyp, as previous studies showed that a (4R)-functionalized proline can destabilize the collagen triple helix, thus resulting in exposing both N–H and CO groups that can also assist in proton conduction.…”
Section: Resultssupporting
confidence: 90%
“…Although the methanesulfonyl group is not an oxo-acid (in oppose to a sulfonic acid), it can still contribute to hydrogen bond formation due to the accessible lone pairs on its oxygens, hence, this is our main suggested explanation for the improved protonic conductivity following the first step of the reaction. This explanation is in line with previous studies showing that groups capable of hydrogen-bonding can support improved proton conduction across biomaterials. , Nevertheless, in our study, we cannot rule out local disruption of the collagen triple helix by adding the methanesulfonyl group to Hyp, as previous studies showed that a (4R)-functionalized proline can destabilize the collagen triple helix, thus resulting in exposing both N–H and CO groups that can also assist in proton conduction.…”
Section: Resultssupporting
confidence: 90%
“…The two peaks at 2941 and 2854 cm –1 were detected as asymmetric C–H stretching vibrations of −CH 3 and −CH 2 , respectively. An obvious stretching vibration peak of −CO at 1702 cm –1 and a bending vibration peak of the −NH bond at 1533 cm –1 were observed. , The absorption peak at 1455 cm –1 belonged to the deformation vibration peak of −CH 2 and the asymmetric deformation vibration peak of −CH 3 . The −NH bond and the −CO bond existed in the generated carbamate bond, which was introduced into KGM-PU and KPU-EG aerogels after cross-linking with hydrophilic isocyanate so that the chemical cross-linking of polyurethane-modified KGM was successful.…”
Section: Resultsmentioning
confidence: 99%
“…We define such an environment as having a solid sample that contains a certain amount of water, and the environment is at a certain RH. To date, most of the reported soft biological materials that show protonic conductivity in these solid-state conditions are either composed of proteins (or peptides) or polysaccharides. , In terms of measured conductivity, most of the multi-SLB films used in this study are at the upper end of reported conductivity values for proteins and polysaccharides, which are typically in the range 0.01–1 mS·cm –1 . The common long-range PT mechanism suggested for all solid-state biological materials is the Grotthuss mechanism.…”
Section: Discussionmentioning
confidence: 99%